PENGARUH PEMBERIAN MINUMAN KUNYIT ASAM TERHADAP PENURUNAN DISMENOREA PRIMER - Achmad, Ismiyanti H.; Hattu, Susana (Jurnal Kebidanan, 2023)
Dysmenorrhea or menstrual pain is a condition in which menstrual flow is difficult (difficult menstrual phase) or painful menstruation (painful menstruation). Menstrual pain is a symptom and not a disease. Dysmenorrhea can be used for menstrual pain that is quite severe where sufferers treat themselves with analgesics or go to the doctor, so this needs to be prevented or treated with non-pharmacology, namely herbal concoction therapy with tamarind turmeric.To determine the effect of giving tamarind turmeric on reducing primary dysmenorrhea in Midwifery Students at the Poltekkes Kemenkes Maluku in 2022.This study used the Quasy Experiment method with a two group pretest and posttest design. In this research design, the subjects were divided into two groups, namely the intervention group and the control group, all of which would be pretested and posttested. The research population is Midwifery Students at the Poltekkes Kemenkes Maluku in 2022, with a total sample of 32 respondents who were taken using a purposive sampling technique.The results of this study indicate that there is an effect of giving turmeric acid on primary dysmenorrhea in the intervention group of D-III Midwifery students at the Poltekkes Kemenkes Maluku in 2022 (p value = 0.000 < ɑ (0.05).There is an effect of giving tamarind turmeric on reducing primary dysmenorrhea.